Childhood Sexual Abuse and Indicators of Immune Activity: A Systematic Review - D'Elia, Ana T. D.; Matsuzaka, Camila T.; Neto, Jair B. B.; Mello, Marcelo F.; Juruena, Mario F.; Mello, Andrea F. (Frontiers in Psychiatry, 2018)
Background: Childhood sexual abuse (CSA) is a prevalent subtype of early life stress associated with changes in immunological and neuroendocrine systems leading to inflammatory responses of the organism and increasing several inflammatory and immune markers. We aimed to conduct a systematic review concerning the association between CSA and indicators of immune activity. Methods: We conducted a search for articles in PubMed, Scopus, PsycINFO, and Web of Science, using the key words: (“Child sexual abuse” OR “childhood maltreatment” OR “sexual violence” OR “posttraumatic stress disorder” OR “rape”) AND (“cytokines” OR “inflammatory markers” OR “interleukin” OR “tumor necrosis factor” OR “C-reactive protein”). PRISMA guidelines were used in order to improve the quality of this research, and MeSH terms were used in PubMed. Results: A total of 3,583 studies were found and, after application of the exclusion criteria, 17 studies were included in this review. Most studies reported an increase of inflammatory activity associated with the presence of early abuse. IL-6, TNF- α, and C-reactive protein were the most frequently analyzed markers and some studies showed higher levels in individuals that suffered CSA compared with controls, although the results were heterogeneous, as was the assessment of CSA, repeated trauma, and time of occurrence. It was not possible to perform a meta-analysis because the results were diversified. Conclusion: CSA is associated with changes in inflammatory markers levels. Improving the assessment of subtypes of trauma is important to further understand the complex correlations of CSA and its biological consequences such as psychiatric and physical illness in later life.